The Influence of Artificial Intelligence (AI) Implementation in the Shopee Application on Consumer Satisfaction in an Islamic Business Perspective with Customer Experience as a Moderating Variable (Study on Students in Bandar Lampung who use Shopee) - Yana, Gusti; Ahmeed, Moh. (Sharia Business Management UIN Raden Intan Lampung, 2024)
Consumer satisfaction can be interpreted as one of the indicators to see the success of a company by the extent to which consumers feel satisfied with the company, therefore it is very crucial for a company to always pay attention to its customers whether they feel very satisfied, satisfied or not satisfied at all. The purpose of this study is to determine whether the application of artificial intelligence has a positive and significant effect on consumer satisfaction. And how the application of artificial intelligence in the shopee application is based on an Islamic business perspective.This study uses a quantitative approach method. The data used is primary data by distributing questionnaires online via google form. The population used in this study were students who used those in Bandar Lampung City. A sample of 97 people using the Probability Sampling formula, taken by simple random sampling with the Cochran technique. Data analysis was processed using SmartPLS version 4.Artificial Intelligence has a positive and significant influence on consumer satisfaction. The Technology Acceptance Model theory explains individual acceptance of information technology systems. Customer experience does not moderate the relationship between AI and consumer satisfaction. However, it is important to pay attention to the application of AI from an Islamic Business perspective because it can affect the law of its use. Thus, the application of AI from an Islamic Business perspective can help provide consumer satisfaction.